D. N. Mamin-Sibiryak in the Diary Reflections of M. M. Prishvin - Medvedev, Aleksandr A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2019)
This article examines previously unstudied Prishvin’s reflection on Mamin-Sibiryak in his Diary of the 1930s–1950s. Prishvin focused on Mamin-Sibiryak’s creative work between the 1930s and 1950s. For Prishvin, Mamin’s texts become the most important source of in-depth understanding of the national and social psychology (value attitudes) of the Russian people and Ural merchants. Prishvin correlates the The Tale of Igor’s Campaign in the “great time” of Russian history with Mamin-Sibiryak’s novel Features from Pepko’s Life (1894), revealing the inherent feeling of patriotism that brings these texts together. Mamin is important for Prishvin as a spokesman for life-affirming trends in literature despite the nihilism of his time. It is important for Prishvin that Mamin, like he himself, avoided both the utopianism of the revolutionary intelligentsia and the utopianism of symbolists in his work. Prishvin destroys the prevailing ideological stereotype about Mamin as a naturalist writer (“Russian Zola”). Prishvin puts Mamin in the same row with Tolstoy and Aksakov, seeing himself as a successor of this line in literature. The figure of Mamin becomes key for Prishvin in his writer’s self-determination and his creative path. Prishvin perceives Mamin as a successor of the tradition of Russian classical literature, which goes back to the ancient Russian tradition (The Tale of Igor’s Campaign). Prishvin’s understanding of the Urals in the perception of Mamin as a “homely province” caused a polemical reaction of P. Bazhov, who interpreted Mamin’s works through the prism of industrial workers’ Urals. During the war, for Prishvin, Mamin’s reflections on the conquest of Siberia by Yermak, which constitute the unofficial historiography of Siberia, become significant. His last diary entries are devoted to Mamin’s 100th birthday where Prishvin argues with the Soviet ideologisation of Mamin.